Medical audit — a preliminary report from general practice - Ryan, M. P. (1979)
As three single-handed practitioners who work in the same health centre, we decided to review our work in clinical management and preventive medicine. We used data contained in a simple medical information system but, where necessary, referred to the original problem-orientated medical records. The results showed that we did not always reach standards which we considered satisfactory but we feel this type of review is worthwhile and could be applied in many general practices.